2012
DOI: 10.1093/aje/kwr471
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity and Body Mass Index and Their Associations With the Development of Type 2 Diabetes in Korean Men

Abstract: The authors examined the independent and combined associations of physical activity and obesity with incident type 2 diabetes among 675,496 Korean men from the database of the National Health Insurance Corporation. During an average follow-up of 7.5 years (1996-2005), 52,995 men developed type 2 diabetes. Men with overweight, obese I, and obese II classifications had 1.47, 2.05, and 3.69 times higher risk of type 2 diabetes, respectively, compared with normal weight men, and men with low, medium, and high acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
0
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 32 publications
3
27
0
2
Order By: Relevance
“…Follow-up time varied from 3 [42] to 23.1 [60] years. Twelve studies were conducted in the USA [12,14,35,38,46,58,[60][61][62][63][64][65], six in Asia [47,57,59,[66][67][68], two in Australia [40,42] and eight across Europe [13,36,37,39,41,[69][70][71]. All cohorts relied on self-reported PA collected using questionnaires or by interview, apart from one study in Hawaiians [58].…”
Section: Resultsmentioning
confidence: 99%
“…Follow-up time varied from 3 [42] to 23.1 [60] years. Twelve studies were conducted in the USA [12,14,35,38,46,58,[60][61][62][63][64][65], six in Asia [47,57,59,[66][67][68], two in Australia [40,42] and eight across Europe [13,36,37,39,41,[69][70][71]. All cohorts relied on self-reported PA collected using questionnaires or by interview, apart from one study in Hawaiians [58].…”
Section: Resultsmentioning
confidence: 99%
“…A list of the excluded studies and the exclusion reasons is found in the Supplemental Table S3. For one study, we used results from a duplicate publication [31] in the subgroup analysis of gender because results were not stratified by gender in the most recent study [62] and for another study we used data from the publication with the largest number of cases for the high versus low analysis [59], but we used data from an overlapping publication [65] for the dose-response analysis because there was not sufficient information in the former publication.…”
Section: Study Selectionmentioning
confidence: 99%
“…4b, Supplemental Table S5). Ten studies (9 publications) [3,16,26,40,41,43,61,65,68] were included in the dose-response analysis of hours per week of leisure-time activity (two of these studies provided only a continuous risk estimate [3,41] ) and the summary RR was 0.75 (95 % CI 0.67-0.85, I 2 = 89 %, p heterogeneity \ 0.0001) per 5 h per week (Fig. 4c).…”
Section: Leisure-time Physical Activitymentioning
confidence: 99%
“…While obesity and physical inactivity are recognised as the main risk factors associated with the increase in diabetes, the role of other determinants that could potentially be corrected more easily is often a subject of current research [1,2].…”
Section: Introductionmentioning
confidence: 99%